Tindak Tutur Dalam Program TV Metro TV Sentilan Sentilun Edisi 16 Januari 2015 Dengan Judul "Ada Gula Ada Mafia" - ARFIANNIE, ANNISA, Prof. Dr. Abdul Ngalim, M.M, M.Hum (2016)
This research purpose was: (1) Description of act to say the locution, ilocution, and perlocution at TV program of Metro TV Sentilan Sentilun Metro TV January, 16 2015 edition with the title "There is Sugar There is Mafia". (2) Description of intend the act to say in third method at TV program of Metro TV Sentilan Sentilun Metro TV January, 16 th 2015 edition with the title "There is Sugar There is Mafia". This research represents descriptive qualitative research with strategy open the language phenomenon of found on research subject. This research object was discourse from TV program of Metro TV Sentilan Sentilun Metro TV January, 16th 2015 edition with the title "There is Sugar There is Mafia". Data was used in this research that was sentence or action to say in TV program of Metro TV Sentilan Sentilun Metro TV January, 16 th 2015 edition with the title "There is Sugar There is Mafia". The data collecting technique in this research was use the correct reading and note technique. While the data analysis technique was use the referensia and pragmatic technique. Referensial technique was used for description of dialogued act to say at TV program of Metro TV Sentilan Sentilun Metro TV January, 16th 2015 edition with the title "There is Sugar There is Mafia", while pragmatic technique was used to explains act to say dialogue contains of locution, ilocution and perlocution and intend the narrator intention. So, can be conclusion that the researcher can found 45 dialogued in TV program of Metro TV Sentilan Sentilun Metro TV January, 16th 2015 edition with the title "There is Sugar There is Mafia", related to acting to say the locution, ilocution and perlocution.